Synthesis and Biological Activity of Diazaphospholo-Iminophosphorane Derivatives of Zidovudine (Azt) Through Staudinger Reaction - A. JANARDHAN RAO; V. KOTESWARA RAO; P. VISWESWARA RAO; B. SATHEESH KRISHNA; C. NAGA RAJU; S. K. GHOSH (International Journal of Pharma and Bio Sciences, 2010)
Synthesis of a series of novel iminophosphorane derivatives of Zidovudine (AZT) was accomplished through Staudinger reaction. In the first step PBr3 was reacted with various substituted phenolic and amino compounds in the presence of triethylamine (TEA) in dry tetrahydrofuran (THF) under nitrogen atmosphere followed by cyclisation of (±) 2-aminomethyl piperidine, afforded diazaphosphole P(III) intermediates (3al).They were further reacted with zidovudine to obtain iminophosphorane derivatives 4a-l. They showed promising antioxidant activitiy. Their antioxidant activitiy was greatly influenced by the presence of different bio-active groups at phosphorus.